ASSESSMENT OF THE INFLUENCE OF FACTORS ON THE SOCIAL-ECONOMIC DEVELOPMENT OF THE REGIONS (Marketing Journal, 2025)
This article systematically analyzes the main factors affecting the socio -economic development of regions. In the study, in particular, the interrelationship between the volume of gross regional product, the volume of construction works and the volume of fixed capital investments and their influence on economic growth rates was studied empirically. Economic activity, the level of infrastructural development and the formation of the investment environment by region were also analyzed, and the contribution of each factor to regional economic growth was evaluated. The results of the research serve to develop practical recommendations for increasing the economic potential of the regions, directing investments effectively, and forming a sustainable socio -economic policy. № 10-SON OKTA BR, 2025 -YIL 282
Keywords: territory; factors; socio -economic development; economic system